Morphological Features of Thyroid Gland in Rats with Experimental Autoimmune Thyroiditis After Administering Cryopreserved Allogeneic Fetal Cells - Karachentsev, Yuriy I.; Malova, Natalya G.; Komarova, Irina V.; Sirotenko, Larisa A.; Sergienko, Larisa Yu.; Ochenashko, Olga V.; Petrenko, Aleksandr Yu. (Problems of Cryobiology and Cryomedicine, 2017)
The designing of novel approaches and search for more efficient means to normalize the thyroid gland (TG) function in autoimmune thyroiditis (AIT) is a topical task in current endocrinology. Here we assessed the effect of cryopreserved allogeneic fetal liver cells (cFLCs) and those of fetal mesodermal tissues (cFMTCs) on thyroid gland (TG) morphostructure in rats with experimental AIT. The cFLCs and cFMTCs were demonstrated to positively affect the TG of rats with induced AIT even at the early stages of the study. Both types of fetal cells potentiated the thyrocyte proliferation and microfollicle differentiation even in 7 days after administration. This effect persisted during a month of observation. Herewith the cells of mesodermal origin had a more pronounced effect than the fetal liver ones. Our findings testify to the prospects of using stem and progenitor cells of fetal origin for AIT correction, that may be the basis in designing a novel efficient approach to the therapy of autoimmune damage of thyroid parenchyma. Probl Cryobiol Cryomed 2017; 27(4): 356-366